2009
DOI: 10.1007/s00253-009-1949-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic diversity in biohydrogenation of polyunsaturated fatty acids by lactic acid bacteria involving conjugated fatty acid production

Abstract: Lactobacillus plantarum AKU 1009a effectively transforms linoleic acid to conjugated linoleic acids of cis -9,trans-11-octadecadienoic acid (18:2) and trans-9,trans-11-18:2 [cis-6,cis-9,cis-12,cis-15-octadecatetraenoic acid (18:4)] were found to be transformed. The fatty acids transformed by the strain had the common structure of a C18 fatty acid with the cis-9,cis-12 diene system. Three major fatty acids were produced from α-linolenic acid, which were identified as cis-9, trans-11,cis-15-18:3, trans-9,trans-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 25 publications
(27 reference statements)
4
54
0
Order By: Relevance
“…2). As we reported previously, C18 fatty acids with Δ9 and Δ12 diene systems such as α-linolenic acid, γ-linolenic acid, and stearidonic acid undergo the same transformations in L. plantarum AKU 1009a (20), indicating that the corresponding intermediates (hydroxy, oxo, conjugated, and partially saturated trans-fatty acids) are produced by the combined actions of these enzymes. The revealed fatty acidsaturation metabolism consists of similar reactions in known fatty acid biosynthesis and degradation pathway; however, it is a pathway that uses only free fatty acids as substrates but not CoA-or acyl carrier protein-activated fatty acids.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…2). As we reported previously, C18 fatty acids with Δ9 and Δ12 diene systems such as α-linolenic acid, γ-linolenic acid, and stearidonic acid undergo the same transformations in L. plantarum AKU 1009a (20), indicating that the corresponding intermediates (hydroxy, oxo, conjugated, and partially saturated trans-fatty acids) are produced by the combined actions of these enzymes. The revealed fatty acidsaturation metabolism consists of similar reactions in known fatty acid biosynthesis and degradation pathway; however, it is a pathway that uses only free fatty acids as substrates but not CoA-or acyl carrier protein-activated fatty acids.…”
Section: Resultsmentioning
confidence: 61%
“…The TMS derivatives were prepared by direct treatment of the purified fatty acid methyl esters with a mixture of TMS agent (pyridine/hexamethyldisilazane/trimethylchlorosilane; 9:3:1, by volume) in screw-cap tubes for 30 min at 60°C, followed by extraction with chloroform. The chemical structures of purified fatty acid methyl esters, pyrrolidide derivatives, and TMS derivatives were determined by mass spectroscopy (MS), and the chemical structures of purified free fatty acids were determined by 2D proton NMR ( 1 H-NMR) techniques including 1 H-1 H double-quantum-filtered chemical-shift correlation spectroscopy and 2D nuclear Overhauser effect spectroscopy, as described previously (20).…”
Section: Purification Of Enzymes From Transformantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This outcome is in line with the observations of Lough and Anderson (1973) and Vanhatalo et al (2007) who reported increased proportions of C18:1trans-11 in grass and red clover silages. The exact origin of C18:1trans-11 in silage is not clear but it was shown by Ogawa et al (2005) and Kishino et al (2009) that LAB can produce this fatty acid. Kishino et al (2009) demonstrated that LAB can isomerise C18:2n-6 into conjugated C18:2 and subsequently hydrogenate this fatty acid into C18:1trans-11.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…The exact origin of C18:1trans-11 in silage is not clear but it was shown by Ogawa et al (2005) and Kishino et al (2009) that LAB can produce this fatty acid. Kishino et al (2009) demonstrated that LAB can isomerise C18:2n-6 into conjugated C18:2 and subsequently hydrogenate this fatty acid into C18:1trans-11. However, this explanation is not in line with the results of the current study Ebrahimi et al LAB, lactic acid bacteria; TFA, total fatty acids; SFA, saturated fatty acids; MUFA, monounsaturated fatty acids; PUFA, polyunsaturated fatty acids; UFA, unsaturated fatty acids.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%